4 - Traditional Authority at the Crossroads of Governance in Republican Cameroon - Cheka, Cosmas (Africa Development, 2021)
The study shows that traditional authority is indeed at the crossroads of governance in republican Cameroon. The citizen is bound by both modern law and traditional values; even if political theorists and leaders of republican institutions take objection to certain traditional values and seem to find difficulty over whether/how to formally integrate traditional authorities into the realm of the republic. Traditional authority incarnates a reassuring institutional stability and certainty to the masses, which elected officers (who come and go) do not provide in republican institutions. The vast majority of the population feels distant from the concept of ‘republic’ at grassroots level, where traditional authority remains the de facto institution of local governance. Based on empirical findings that highlight the important role that traditional authorities play in local development, the paper submits that traditional authorities should be formally integrated into the republican institutional setting by effectively constituting the first level of decentralized institutions of governance.